2000
DOI: 10.1063/1.1288168
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical diagnosis of oxide traps formed during reactive ion etching

Abstract: Oxide traps generated by reactive ion etching are studied using a pulsed femtosecond laser. The second harmonic generation ͑SHG͒ signal from the Si/SiO 2 interface is sensitive to charged traps in the oxide. The time evolution of the SHG signal indicates that positive traps predominate. The angular dependence of the polarized signal shows that the electric field generated by the oxide traps alters the symmetry of the sample. The damage is greatest for an oxide thickness of 13 nm ͑for a plasma dc bias of 300 V͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…29 However, in a study of plasma etching of thermallygrown SiO 2 on Si͑100͒, SHG-RA patterns were found to "deteriorate" with oxide thinning. 22 "Deterioration" exhibited itself through a reduction of the anisotropic contribution in the SHG-RA signal, i.e. the ratio ͉A / B͉ increased with the etching time.…”
Section: A Estimates Of Interface "Roughness"mentioning
confidence: 98%
See 2 more Smart Citations
“…29 However, in a study of plasma etching of thermallygrown SiO 2 on Si͑100͒, SHG-RA patterns were found to "deteriorate" with oxide thinning. 22 "Deterioration" exhibited itself through a reduction of the anisotropic contribution in the SHG-RA signal, i.e. the ratio ͉A / B͉ increased with the etching time.…”
Section: A Estimates Of Interface "Roughness"mentioning
confidence: 98%
“…Remarkably, after a complete oxide removal, the ͉A / B͉ ratio again became close to the value determined on oxide prior to the plasma etch. 22 The "deterioration" of SHG-RA was attributed to the creation and non-uniform distribution of defects capable of charge trapping in the oxide layer. 22 Clearly, this study suggests that the ͉A / B͉ ratio can be affected by factors other than interface topological roughness.…”
Section: A Estimates Of Interface "Roughness"mentioning
confidence: 99%
See 1 more Smart Citation
“…EFISH adds to the usual second harmonic field of the semiconductor in the absence of an electric field, as shown in Eq. ͑1͒: [7][8][9][10] I͑2͒ ϰ ͉P 2 + P 2 EFISH ͉ 2 = ͉ ͑2͒ + ͑3͒ E DC ͉ 2 I 2 ͑͒, ͑1͒…”
mentioning
confidence: 99%
“…[11][12][13] Also the surface of clean and H terminated c-Si has been studied thoroughly with SHG. [14][15][16][17][18][19][20] In these studies the SHG signal from the c-Si surface has been shown to be sensitive to surface Si dangling bonds for photon energies in the range of ϳ1.0 to ϳ 1.3 eV.…”
Section: Introductionmentioning
confidence: 99%